LITERATURE REVIEW: UTILIZATION OF SALTED EGGSHELL WASTE IN THE DEVELOPMENT OF HALAL COSMETICS FROM CHEMICAL, BIOLOGICAL, AND SHARIA FINANCING PERSPECTIVES - Rizki, S.Pd., M.Sc., Cut Novrita; Mawardah, Mawardah; Hidayat, M. Naufal (Jurnal Biologi Sains dan Kependidikan, 2025)
This study aims to examine the potential utilization of salted duck eggshell waste in the development of halal cosmetics through a literature review approach that integrates chemical, biological, and sharia-compliant financing perspectives. Globally, the increasing demand for natural-based halal cosmetics necessitates innovation in sourcing safe, high-quality, and environmentally friendly raw materials. Salted eggshells, which are commonly regarded as household or food-industry waste, have been shown to contain high levels of calcium carbonate as well as membranes rich in bioactive proteins such as collagen-like molecules and glycoproteins, making them promising candidates for skincare applications. The literature indicates that the biominerals and bioactive compounds within eggshells can enhance halal cosmetic formulations, although applied research remains limited to laboratory-scale studies. Beyond technical considerations, this study highlights the importance of sharia-based financing models—such as musyarakah and mudharabah—in supporting MSMEs to develop competitive waste-derived products, particularly in regions with abundant raw material availability, such as Banda Aceh. Overall, this study underscores the need for multidisciplinary integration to realize sustainable halal cosmetic innovations that hold the potential to become new industry opportunities within a circular economy framework